2017
DOI: 10.3748/wjg.v23.i44.7813
|View full text |Cite
|
Sign up to set email alerts
|

Advances in endoscopic balloon therapy for weight loss and its limitations

Abstract: The field of medical and surgical weight loss is undergoing an explosion of new techniques and devices. A lot of these are geared towards endoscopic approaches rather than the conventional and more invasive laparoscopic or open approach. One such recent advance is the introduction of intrgastric balloons. In this article, we discuss the recently Food and Drug Administration approved following balloons for weight loss: the Orbera™ Intragastric Balloon System (Apollo Endosurgery Inc, Austin, TX, United States), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…The initial phase of the REDUCE Pivotal trial demonstrated that gastric ulcers occur frequently in these patients but usually do not cause important bleeding complications [5]. Patients who undergo IGB insertion need careful follow-up post insertion and systematic reporting to determine complication rates [6,7]. Additionally, these balloons should not stay in place for more than six months, and patients should be educated about regular follow up.…”
Section: Discussionmentioning
confidence: 99%
“…The initial phase of the REDUCE Pivotal trial demonstrated that gastric ulcers occur frequently in these patients but usually do not cause important bleeding complications [5]. Patients who undergo IGB insertion need careful follow-up post insertion and systematic reporting to determine complication rates [6,7]. Additionally, these balloons should not stay in place for more than six months, and patients should be educated about regular follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Three intragastric balloon devices are currently approved by the FDA in the United States: Orbera Intragas Balloon System (Apollo Endosurgery Inc, Austin, TX, United States), ReShape® Integrated Dual Balloon System (ReShape Medical, Inc., San Clemente, CA, United States), and Obalon (Obalon® Therapeutics, Inc.). These devices are indicated for patients with Class 1 and 2 obesity (BMI 30-40 kg/m 2 ) [2].…”
Section: Discussionmentioning
confidence: 99%
“…Once this is achieved, the catheter is used to inject gas (mixture of nitrogen-sulfur hexafluoride) into the flask. Each flask has a volume of approximately 250 mL, totaling 750 mL with 3 flasks [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual balloon design reduces the risk of prosthesis migration and is retrieved 6 months after placement. 22 The REDUCE pivotal trial was a prospective, randomized controlled trial published in 2015 that was conducted to evaluate the safety and efficacy of the Reshape procedure. Patients undergoing the procedure were found to have a decreased 25.1% %EWL compared with 11.3% for the control group (intention-to-treat).…”
Section: Reshape Duo Igbmentioning
confidence: 99%